Mechanics analysis on the conditions of rock burst occurrence in the coal mass of roadway rib - 陈学华 邓小林 李中华 (Journal of coal science & engineering, China, 2008)
According to the rock burst features occurred in the coal mass of roadway rib in one mine, the mechanics model of coal mass and roof structure system along the edge of goaf was founded to analyze the stress of roof rock layer, so the subside curve of roof rock layer was deduced. Furthermore, the stability of coal and rock system were analyzed, the critical load and critical resistance zone were used to judge the danger degree of rock burst occurrence. The influence of coal mass strength, brittleness degree, coal seam thickness, roof thickness, suspending length, equivalent shear module on the critical load, critical resistance zone was confirmed. So the rock burst occurrence conditions of coal mass in roadway rib mainly depend on mining depth, coal seam thickness and hard roof and floor, which are decided by the above studies, and successfully applied in prediction and prevention of rock burst in this mine.